Comparison of Employee Tenure on Employee Productivity - Ahmad Isa Fitra Ikhwanda Batistuta; Rini Safitri (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This study aims to explore differences in employee productivity levels based on tenure, revealing that employees with less than three years of service generally exhibit lower productivity compared to their more seasoned counterparts. The research was conducted at PT Didu Indonesia, focusing specifically on a comparative analysis of productivity between employees with tenure under three years and those with tenure exceeding three years. Employing a quantitative research design, the study utilized secondary data, comprising productivity records from 60 employees categorized by tenure from 2021-2023. Data analysis was performed using SPSS, with the Kolmogorov Smirnov test yielding a statistic of 3.873 and an asymptotic significance (2-tailed) of 0.000. Since this result is below the 0.05 threshold, the null hypothesis (H0) was rejected in favor of the alternative hypothesis (H1), confirming that the productivity levels between the two groups are significantly different. The implications of these findings are significant for human resource management and organizational strategies. The observable gap in productivity based on tenure suggests that companies should consider implementing tailored onboarding and mentorship programs for new employees to enhance their productivity more swiftly. Fostering a supportive work environment that facilitates skill development and knowledge transfer is crucial. Moreover, identifies a need for ongoing training and professional development opportunities tailored to employees with varying levels of tenure. Organizations can ultimately benefit from recognizing the contributions of long-tenured employees, utilizing their experience as mentorship resources while investing in the growth of newer employees to bridge the productivity gap. By addressing these dynamics, PT Didu Indonesia and similar organizations can create a more cohesive, productive workforce that enhances overall organizational performance and job satisfaction.